Pengawasan dan Hubungan dengan Eefektivitas Kerja Pegawai Pada Kantor Wilayah Badan Pertahanan Nasional Provinsi Maluku - Gustia, Gustia; Sahetapy, Petronela; Rahanra, Ivonni Y (Journal of Government Science Studies, 2023)
Primary data collection was carried out through a list of questions to a number of respondents who were directly involved in research on Supervision and its Relationship with Employee Work Effectiveness at the Regional Office of the National Land Agency of Maluku Province. The results showed that the magnitude of the correlation coefficient between the two main variables in this study was 0 .48 and is in a moderate position. Furthermore, to find out whether there is a significant relationship between the two variables or not, it is necessary to test it by comparing it with the r-Product Moment value at a significant level of 0.5% (95% confidence level). The result is 0.266.s. Thus the results show that the t-table is greater than the r-table value (0.48 > 0.226), so it can be said that the better the supervision carried out by the Head of the Regional Office, the more effective the work of employees at the Regional Office of the National Land Agency will increase Maluku Province. Conversely, if the supervision carried out by the Head of the Regional Office is not carried out properly, then the work effectiveness of employees at the Regional Office of the National Land Agency of Maluku Province will decrease